The Roads to Congress 2016 American Elections in a Divided Landscape (Springer International Publishing, 2018)
This book analyzes both local and national House and Senate campaigns in the 2016 election to reveal how distinctive campaign dynamics have a collective national impact. Featuring detailed case studies of ten competitive House races and twelve high-profile U.S. Senate campaigns, the volume provides a deep analysis of campaign dynamics and the polarizing effects of the presidential campaigns of Donald Trump and Hillary Clinton. These studies are contextualized by four thematic chapters that cover the most salient talking points of the 2016 elections, including voter registration laws and congressional candidates' use of Twitter. As penetrating as it is comprehensive, this volume provides readers with a fuller understanding of the dynamics surrounding contemporary American political campaigns. .